Neuropsychiatric Symptom Burden across Neurodegenerative Disorders and its Association with Function. (May 2023) - Kapustin, Daniel; Zarei, Shadi; Wang, Wei; Binns, Malcolm A.; McLaughlin, Paula M.; Abrahao, Agessandro; Black, Sandra E.; Borrie, Michael; Breen, David; Casaubon, Leanna; Dowlatshahi, Dar; Finger, Elizabeth; et al.
Objective: Neuropsychiatric symptoms (NPS) are prevalent in neurodegenerative disorders, however, their frequency and impact on function across different disorders is not well understood. We compared the frequency and severity of NPS across Alzheimer's disease (AD) (either with mild cognitive impairment or dementia), Cerebrovascular disease (CVD), Parkinson's disease (PD), frontotemporal dementia (FTD), and amyotrophic lateral sclerosis (ALS), and explored the association between NPS burden and function. Methods: We obtained data from Ontario Neurodegenerative Disease Research Initiative (ONDRI) that included following cohorts: AD ( N = 111), CVD ( N = 148), PD ( N = 136), FTD ( N = 50) and ALS ( N = 36). We compared the frequency and severity of individual NPS (assessed by the neuropsychiatric inventory questionnaire) across cohorts using generalized estimating equations and analysis of variance. Second, we assessed the relationship of NPS burden with instrumental (iADLs) and basic (ADLs) activities of living across cohorts using multivariate linear regression while adjusting for relevant demographic and clinical covariates. Results: Frequency of NPS varied across cohorts (χ 2 (4) = 34.4, p < .001), with post-hoc tests showing that FTD had the greatest frequency as compared to all other cohorts. The FTD cohort also had the greatest severity of NPS ( H (4) = 34.5, p < .001). Further, there were differences among cohorts in terms of the association between NPS burden and ADLs ( F (4, 461) = 3.1, p = 0.02). Post-hoc comparisons suggested that this finding was driven by the FTD group, however, the differences did not remain significant following Bonferroni correction. There were no differences among cohorts in terms of the association between NPS burden and IADLs. Conclusions: NPS frequency and severity are markedly greater in FTD as compared to other neurodegenerative diseases. Further, NPS burden appears to be associated differently with function across neurodegenerative disorders, highlighting the need for individualized clinical interventions.